“The Scottish novelist William Black”: Close Appositions and the Modification of Proper Names - Manon Philippe (Anglophonia)
Within the category of nouns, proper nouns have regularly been regarded as alienated from the typical, common nouns and this results in them being given an often-unjustified linguistic special treatment. One example of this isolating process is the analysis of the syntactic form [DET + (common) nominal + Proper Noun] as a case of close apposition (CA), an unnecessary label for a form that otherwise illustrates a kind of nominal modification. This paper presents three main CA types – namely titles, pseudo-titles and prototypical appositions – and then questions this classification as well as the relevance of ordering these forms along a gradient from modification to “pure” apposition (as presented by Meyer (1992)). Studying the pragmatic values of these CA types – old vs. new information, thematic vs. rhematic elements, contrastive and metalinguistic uses, descriptive identification – then paves the way for a comparison between these forms and their analysis as a single modified NP.